The Technology Pedagogy Knowledge (TPK) Teacher Using Worksheet 3D Pageflip Professional for Promoting Argumentation Skills High-Schools Students in Physics Learning - Depi Oktasari; Heru Kuswanto; Ismet Ismet; Sardianto M.S. (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
The demands of 21st-century skills highlighted the importance of cooperation between teachers and students to achieve the expected skill. The Pedagogical knowledge of teachers in teaching and technology into things that need to be developed. The pedagogic ability of teachers in the use of technology can be a potential to develop students' abilities argument. This study aims to develop students' ability argumentation through pedagogical knowledge of teachers in using technology. The technology used is the result of the development of student worksheets 3D PageFlip Impulse and Momentum topics. The purpose of this study to look at the ability of students through the application of scientific argumentation (Technological Pedagogic Knowledge) TPK teachers in the classroom. This research is descriptive research. The data collection capability student argumentation performed by administering a written test. The subjects were students of class X at SMAN 1 Yogyakarta Prambanan. Rate scientific argumentation ability of students refers to Toulmin Argumentation Pattern (TAP). The results showed that the complexity of argumentation ability of students still at low level. These results suggest that the ability of the student arguments need to be improved.